PENGARUH KESADARAN DIRI DAN KEMATANGAN BERAGAMA TERHADAP KOMITMEN ORGANISASI KARYAWAN RSUD TUGUREJO SEMARANG - Agus Riyadi; Hasyim Hasanah (Psympathic : Jurnal Ilmiah Psikologi, 2015)
This study was aimed to measure the effect of self-awareness on organizational commitment, to measure the effect of religious maturity toward organizational commitment, and to measure the influence of self-awareness and religious maturity toward organizational commitment of employees the Tugurejo Hospital in Semarang. Subjects were 187 employee with criterion of Muslim and civil servant (PNS). The study used simple regression analysis to measure the effect level between self-awareness and organizational commitment as well as religious maturity and organizational commitment, while to measure the jointly influence of self-awareness and religious maturity toward organizational commitment used multiple regression analysis. The results covered (1) self-awareness has a positive and significant effect on organizational commitment (2) religious maturity has a positive and significant impact on organizational Commitment (3) Self-awareness and religious maturity jointly have positive and significant impact on organizational commitment. It concluded that self-awareness and religious maturity can be used as predictors to increase employees' organizational commitment.